Oligodendrogenesis in the normal and pathological central nervous system - El Waly, Bilal; Macchi, Magali; Cayre, Myriam; Durbec, Pascale (Frontiers in Neuroscience, 2014)
Oligodendrocytes (OLGs) are generated late in development and myelination is thus a tardive event in the brain developmental process. It is however maintained whole life long at lower rate, and myelin sheath is crucial for proper signal transmission and neuronal survival. Unfortunately, OLGs present a high susceptibility to oxidative stress, thus demyelination often takes place secondary to diverse brain lesions or pathologies. OLGs can also be the target of immune attacks, leading to primary demyelination lesions. Following oligodendrocytic death, spontaneous remyelination may occur to a certain extent. In this review, we will mainly focus on the adult brain and on the two main sources of progenitor cells that contribute to oligodendrogenesis: parenchymal oligodendrocyte precursor cells (OPCs) and subventricular zone (SVZ)-derived progenitors. We will shortly come back on the main steps of oligodendrogenesis in the postnatal and adult brain, and summarize the key factors involved in the determination of oligodendrocytic fate. We will then shed light on the main causes of demyelination in the adult brain and present the animal models that have been developed to get insight on the demyelination / remyelinations process. Finally, we will synthetize the results of studies searching for factors able to modulate spontaneous myelin repair.